DESIGN MECHANISM OF PLAYERS’ COORDINATION IN DYNAMIC GAME FOR MAXIMIZING THE EFFECTIVENESS OF THEIR INTERACTIONS - Artem O. Pichugin; Alexander N. Romannikov (Статистика и экономика, 2016)
Quite often within the activity subjects are compelled to interact with other subjects of one system. And this interaction can have antagonistic character in spite of the fact that they are within one system, and game by which interaction in systems is described, isn’t game with the zero sum. In the article the mechanism which allows to change interaction of players from antagonism to cooperation is offered.